The profile of inflammatory extracellular vesicles in intracerebral hemorrhage patients - Sawant, Harshal; Bihl, Trevor; Nguyen, Doan; Iwuchukwu, Ifeanyi; Bihl, Ji (Frontiers in Stroke, 2022)
Background: Intracerebral hemorrhage (ICH) is one of the leading life-threatening types of strokes with high mortality. A prominent feature of ICH is neuroinflammation involving leukocytes, such as neutrophils and macrophages. Large extracellular vesicles (lEV) and small extracellular vesicles (sEV) released from various cells are used as biomarkers for different diseases. Here, we aimed to determine the concentration/population of lEV and sEV from different leukocytes in ICH patients and analyze the correlation of these lEV/sEV with clinical parameters. Methods: lEV and sEV were isolated from the plasma of ICH patients (n=39) by using the serial centrifuge methods. Nanoparticle tracking analysis (NTA, NS300) was used to determine the type and concentration of different leukocytes-released lEV/sEV. Specific antibodies, CD66b, P2RY12, and CD80 were used for different leukocyte types. Results: A predictive relationship between both hospital length of stay (R2=0.83) and Intensive care units (ICU) length of stay (R2=0.88) was found with lEV and sEV and patient data [including low-density lipoprotein (LDL), ICH volume, etc.]. Further predictive multiple linear regression relationship was seen between lEV and sEV concentrations and MRSV3 (Modified Rankin Scale at 90 days) (R2=0.46) and MRSV5 (Modified Rankin Scale at 180 days) (R2=0.51). Additionally, a slight, but statistically significant (p=0.0151), multiple linear regression relationship was seen between lEV and sEV concentrations and ICU length of stay (R2=0.26). Conclusion: This study found predictive relationships between patient outcomes and lEV and sEV. When combined with generally collected patient data (LDL, etc.), measurements of lEV and sEV are strongly predictive of overall patient outcome. Further, larger studies should investigate these effects.